2018
DOI: 10.1080/02602938.2018.1434610
|View full text |Cite
|
Sign up to set email alerts
|

Exploring tertiary English as a Foreign Language writing tutors’ perceptions of the appropriateness of peer assessment for writing

Abstract: Despite the increasing volume of research in peer assessment for writing, few studies have been conducted to explore teachers' perceptions of its appropriateness for local writing instruction. It is essential to understand teachers' perceptions of peer assessment as teachers play an important role in whether and how peer assessment would be implemented in their instruction. The current study investigated tertiary English writing tutors' perceptions of the appropriateness of peer assessment for EFL writing in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Total 26 When the focus of peer interaction was examined, Figure 3 revealed the prominent roles of wording and grammar across the three interaction patterns. It might be due to the essential role of language accuracy in examination essays and the prolonged examinationoriented culture of learning in China (Zhao, 2018). Nevertheless, Figure 3 showed that students also commented areas on the global level: organisation in the collaborative and expert/novice patterns, styles in the collaborative and dominant/dominant patterns, and content in all the three patterns.…”
Section: Amount and Focus Of Oral Peer Feedback Across Interaction Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Total 26 When the focus of peer interaction was examined, Figure 3 revealed the prominent roles of wording and grammar across the three interaction patterns. It might be due to the essential role of language accuracy in examination essays and the prolonged examinationoriented culture of learning in China (Zhao, 2018). Nevertheless, Figure 3 showed that students also commented areas on the global level: organisation in the collaborative and expert/novice patterns, styles in the collaborative and dominant/dominant patterns, and content in all the three patterns.…”
Section: Amount and Focus Of Oral Peer Feedback Across Interaction Pamentioning
confidence: 99%
“…All participants were aged 19. The students had very limited experience of peer review due to their prolonged teacher-centred and examination-driven education experience in China (Berry, 2011;Zhao, 2018). Therefore, to improve the quantity and quality of peer feedback (Rahimi, 2013;Yang & Meng, 2013;Zhao, 2014), an approximately 20 minute training session was provided by the writing tutor prior to each peer review activity.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This student-led learning practice is also endorsed as positive for students to take the roles and responsibilities of assessors; hence, students might attain the levels of higher-order thinking skills, particularly reasoning and argumentation (Lin & Xiang, 2019;Lu & Xie, 2019). Despite the potential benefits of peer feedback, accumulated empirical evidence has arisen a number of problems related to the hesitations of incorporating peer feedback into the instructions and learning process (Panadero, 2016;Zhao, 2018;Zhu & Carless, 2018). A key challenge lies in trust issues associated with peers' abilities because peer comments merely highlight surface problems (e.g., idea development, essay structure) rather than yielding marked learning improvements (e.g., vocabulary richness, grammar accuracy).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the students' capability and psychology in assessing peer's writing must be paid attention. The previous studies found that the students lacked confidence in delivering their opinion or feedback in the process of PA because of their capability in assessing their peers' writing (Cheng and Warren, 2005;Topping, 2003;Zhao, 2018). To overcome these problems, the teacher should design the instrument well (Ohland et al, 2012).…”
Section: A Introductionmentioning
confidence: 99%